Kindness in short supply: Evidence for inadequate prosocial input. (December 2022) - Abel, Jennifer E.; Vani, Preeti; Abi-Esber, Nicole; Blunden, Hayley; Schroeder, Juliana
Abstract: In everyday life, people often have opportunities to improve others' lives, whether offering well-intentioned advice or complimenting someone on a job well done. These are opportunities to provide "prosocial input" (information intended to benefit others), including feedback, advice, compliments, and expressions of gratitude. Despite widespread evidence that giving prosocial input can improve the well-being of both givers and recipients, people sometimes hesitate to offer their input. The current paper documents when and why people fail to give prosocial input, noting that potential givers overestimate the costs of doing so (e.g., making recipients uncomfortable) and underestimate the benefits (e.g., being helpful) for at least four psychological reasons. Unfortunately, the reluctance to give prosocial input results in a short supply of kindness.